Pengembangan Media Video Pembelajaran Berbasis Budaya untuk Meningkatkan Hasil Belajar Siswa Kelas V SD: Development of Culture-Based Learning Video Media to Improve Learning Outcomes of Grade V Elementary School Students - Jaya, Andrean; Habib, Mustafa; Sugma, Azri Ranuwaldy (ITScience (Information Technology and Science), 2024)
In the learning process, teachers still use learning that is carried out using lectures and guided by textbooks and LKS media; the use of media is still not optimal and varied, so learning tends to be monotonous and can make students bored. This study uses a type of development research (research and development) concerning the ADDIE model, which consists of 5 stages: analysis, design, development, implementation, and evaluation. The subjects of this study were students of grade V SDN 050659 Stabat. The data collection method in this study was obtained from interviews, questionnaires, and documentation. Data analysis of this study was obtained from a validity questionnaire from material and media experts. The practicality criteria were obtained from teacher response questionnaires and student response questionnaires. The results of the product eligibility by validity from material experts obtained a percentage value of 92% with a very valid category; media experts obtained a percentage value of 91% with a very valid category. The teacher response questionnaire obtained a percentage of 90% with a very valid category, the results of the large group trial obtained a percentage of 90% with a very valid category, and the results of the large group trial obtained a percentage of 90% with a very valid category. The study's results found that learning using culture-based learning video media that has been developed can help students be active and effective in the learning process.